Discovery of a New Compound, Erinacerin W, from the Mycelia of Hericium erinaceus, with Immunomodulatory and Neuroprotective Effects - Lin, Jing-Yi; Chen, Yen-Po; Lin, Ting-Wei; Li, Tsung-Ju; Chen, Yu-Wen; Li, I-Chen; Chen, Chin-Chu (Molecules (Basel, Switzerland), 2024)
One new compound with an isoindolinone skeleton, along with erinacines A, C, and S, was isolated from the mycelia of Hericium erinaceus, an edible fungus with a long history of use in traditional Chinese medicine. Based on analysis of MS and NMR spectral data, the structure of the compound was identified as (2E,6E)-8-(2-(1-carboxy-3-methylbutyl)-4,6-dihydroxy-1-oxoisoindolin-5-yl)-2,6-dimethylocta-2,6-dienoic acid. In light of this discovery, we have given this compound the name erinacerin W. Using a co-culture in vitro LPS-activated BV2 microglia-induced SH-SY5Y neuroinflammation model, the results showed that erinacerin W demonstrated protection against the LPS-activated BV-2 cell-induced overexpression of IL-6, IL-1β, and TNF-α on SH-SY5Y cells. This finding may provide potential therapeutic approaches for central nervous disorders.